Rancangan Alat Bantu Pada Proses Produksi Tali Kur - Mauluddin, Yusuf; Hidayatullah, Anung Andi; Dara, Putri (Jurnal Kalibrasi, 2025)
MSMEs (Micro, Small, and Medium Enterprises) often face challenges in meeting growing market demands. One of the main issues is the inability to balance workload, which causes employees to work harder to achieve production targets. This increases the risk of worker fatigue and can reduce quality and productivity. This study aims to analyze the work system and identify improvement solutions to increase production capacity and reduce physical workload. Using the Macroergonomics Analysis and Design (MEAD) method, this study identified factors that affect worker performance, such as organization, equipment, physical environment, and working conditions. The results showed that improving the work system through the design of tools and workbenches can shorten the som sewing process time from an average of 900 seconds to 11 seconds, increasing production capacity from 8,120 pcs to 28,000 pcs. In addition, employees' physical workload was also reduced, which was validated using RULA, where the initial risk score decreased from 5 (medium risk) to 3 (low risk) after the improvement.